Relationship of Circulating Growth and Differentiation Factors 8 and 11 and Their Antagonists as Measured Using Liquid Chromatography–Tandem Mass Spectrometry With Age and Skeletal Muscle Strength in Healthy Adults. (14th December 2018) - Semba, Richard D; Zhang, Pingbo; Zhu, Min; Fabbri, Elisa; Gonzalez-Freire, Marta; Carlson, Olga D; Moaddel, Ruin; Tanaka, Toshiko; Egan, Josephine M; Ferrucci, Luigi
Abstract: Background: Growth and differentiation factors 8 (GDF8) and 11 (GDF11) have attracted attention as targets for rejuvenating interventions. The biological activity of these proteins may be affected by circulating antagonists such as their respective prodomains, follistatin (FST315), WFIKKN1, and WFIKKN2. Reports of the relationship of GDF8 and GDF11 and their antagonists with aging and aging phenotypes such as skeletal muscle strength have been conflicting possibly because of difficulties in measuring these proteins and polypeptides. Methods: Plasma GDF8 and GDF11 and their antagonists were measured using a multiplexed selected reaction monitoring assay and liquid chromatography–tandem mass spectrometry in 160 healthy adults aged 22–93 years. Quadriceps strength was measured by knee extensor torque using isokinetic dynamometry. Results: Spearman correlations with age were the following: GDF11 prodomain ( r = .30, p = .001), GDF11 mature protein ( r = .23, p = .004), FST315 ( r = .32, p < .0001), WFIKKN1 ( r = −.21, p = 0.008), and WFIKKN2 ( r = .18, p = .02). Independent of age, FST315 and WFIKKN1 were negatively associated with knee strength ( p = .02, p = .03, respectively) in a multivariable model that included both GDF8 and GDF11 mature proteins. Conclusions: When measured by an antibody-free selected reaction monitoring assay, GDF8, GDF11, and their antagonists are found in the circulation in the ng/mL range. In healthy adults, plasma GDF11 and antagonists FST315, WFIKKN1, and WFIKKN2 differed by age. Antagonists of GDF8 and GDF11, but not GDF8 and GDF11, were independently associated with skeletal muscle strength. Further work is needed to characterize the relationship of these protein and polypeptides with sarcopenia-related phenotypes such as physical function and walking disability.